2001
DOI: 10.1046/j.1365-2095.2001.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Urea in feeds for sea water farmed Atlantic salmon: effect on growth, carcass quality and outbreaks of winter ulcer

Abstract: The main objective of the present study was to evaluate whether dietary supplementation of urea might reduce the incidence of winter ulcer in sea water-farmed Atlantic salmon. Salmon destined to be S0 smolt were fed with a urea-supplemented diet (0 or 20 g kg )1 urea) over an 8-week period prior to sea water transfer and were then fed supplemented diet (0, 5, 10 or 20 g kg )1 urea) during the ®rst and second winters in the sea. During the ®rst winter positive relationships between dietary urea and plasma urea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
0
1
2
Order By: Relevance
“…The present blood plasma osmolality and muscle moisture content in the Atlantic salmon after 39 h of chilling, therefore, are consistent with results showing that salmon may survive at subzero temperatures. However, the relatively stable seawater adaptation throughout the present study, seems to contradict the dramatic changes reported by Lega et al (1992), who showed blood plasma osmolality >400 mosmol l 1 at 1 C in post-smolts averaging 121 g. Since substantially larger salmon were tested in the present study, the difference may be explained by fish size which is consistent with increased salinity tolerance with increasing fish size in many salmonid species (Parry, 1958;Houston, 1961;Conte & Wagner, 1965;Landless, 1976;Johnsen & Clarke, 1988;Rørvik et al, 2000bRørvik et al, , 2001. This may be partly due to growth regulating factors control by the maturation of the hypo-osmoregulatory system (Conte, 1969).…”
Section: Discussioncontrasting
confidence: 69%
“…The present blood plasma osmolality and muscle moisture content in the Atlantic salmon after 39 h of chilling, therefore, are consistent with results showing that salmon may survive at subzero temperatures. However, the relatively stable seawater adaptation throughout the present study, seems to contradict the dramatic changes reported by Lega et al (1992), who showed blood plasma osmolality >400 mosmol l 1 at 1 C in post-smolts averaging 121 g. Since substantially larger salmon were tested in the present study, the difference may be explained by fish size which is consistent with increased salinity tolerance with increasing fish size in many salmonid species (Parry, 1958;Houston, 1961;Conte & Wagner, 1965;Landless, 1976;Johnsen & Clarke, 1988;Rørvik et al, 2000bRørvik et al, , 2001. This may be partly due to growth regulating factors control by the maturation of the hypo-osmoregulatory system (Conte, 1969).…”
Section: Discussioncontrasting
confidence: 69%
“…Outras aplicações incluem sua utilização na determinação da estabilidade e na estimativa da vida útil de produtos, especialmente dos alimentos e bebidas (STONE & SIDEL, 1998). A ADQ foi empregada na avaliação de salmão do atlântico defumado, fermentado e curado (MORZEL et al, 1999), na avaliação do reflexo de uma dieta rica em uréia na qualidade da carne do salmão do Atlântico (RORVIK et al, 2001) e em truta do ártico -Salvelinus alpinus (GINÉS et al, 2004). O presente trabalho objetivou, a partir de métodos físico-químicos e sensoriais, avaliar o estado de conservação da corvina armazenada em diferentes períodos a 0°C.…”
unclassified
“…Este método já foi empregado na avaliação de salmão (MORZEL et al, 1999;RORVIK et al, 2001) e de corvina (BORGES et al, 2007;TEIXEIRA, 2005).…”
Section: Revisão De Literaturaunclassified